Targets and mechanisms of berberine,a natural drug with potential to treat cancer with special focus on breast cancer - Kaboli, Parham Jabbarzadeh; Rahmat, Asmah; Ismail, Patimah; Ling, King Hwa (Elsevier, 2014)
Breast cancer is the most common cancer among women worldwide and novel therapeutic agents are needed to treat this disease. The plant-based alkaloid berberine has potential therapeutic applications for breast cancer, although a better understanding of the genes and cellular pathways regulated by this compound is needed to define the mechanism of its action in cancer treatment. In this review, the molecular targets of berberine in various cancers, particularly breast cancer, are discussed. Berberine was shown to be effective in inhibiting cell proliferation and promoting apoptosis in various cancerous cells. Some signaling pathways affected by berberine, including the MAP (mitogen-activated protein) kinase and Wnt/β-catenin pathways, are critical for reducing cellular migration and sensitivity to various growth factors. This review will discuss recent studies and consider the application of new prospective approaches based on microRNAs and other crucial regulators for use in future studies to define the action of berberine in cancer. The effects of berberine on cancer cell survival and proliferation are also outlined.